2018
DOI: 10.3390/met8100769
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Spray Coatings as an Adhesion Promoter in Metal/FRP Joints

Abstract: In this study, various structuring methods for creating adhesion by mechanical interlocking in the interface of metal/FRP (fiber-reinforced polymer) joints are investigated. A novel processing route using thermal spray coatings as additive structure is presented. Different coating systems are first assessed by axial loading tests with spray-coated plungers for the evaluation of the additive layer adhesion on the metallic base material. Additional microstructures, produced by different abrasive processes (corun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Since the strength between coating and polymer mainly depends on the surface structure, the achieved lap shear strength in connection with PA6GF47BD varied only within a small range of 19.7 ± 0.4 MPa and 21.0 ± 0.7 MPa (Figure 4b). This is roughly in the range of 24 MPa that were reported in a recent study for the shear strength between fiber-reinforced polyamide 6 and NiAl5 coatings [27]. The heating experiments revealed a strong influence of the coating thickness on the heating rate.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Since the strength between coating and polymer mainly depends on the surface structure, the achieved lap shear strength in connection with PA6GF47BD varied only within a small range of 19.7 ± 0.4 MPa and 21.0 ± 0.7 MPa (Figure 4b). This is roughly in the range of 24 MPa that were reported in a recent study for the shear strength between fiber-reinforced polyamide 6 and NiAl5 coatings [27]. The heating experiments revealed a strong influence of the coating thickness on the heating rate.…”
Section: Resultssupporting
confidence: 74%
“…Thermal spray coatings provide a rough and undercut surface. Hence, they can be used as adhesion promoter for polymer-metal hybrids, reaching an interlaminar strength higher than mechanically blasted metallic surfaces [17,26,27]. When the coating is applied without prior activation of the substrate, residual stresses due to mechanical blasting can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal spraying process is based on the findings of Lindner et al [14] and Saborowski et al [17], who identified a NiAl5 coating suitable for creating good adhesion between aluminum and PA6. The resulting surface is characterized by a high roughness as well as the formation of undercuts.…”
Section: Methodsmentioning
confidence: 99%
“…As an additive structuring method, thermal spraying provides an irregular, rough, and undercut surface. Utilizing a NiAl5 coating, Lindner et al [14] reported a lap shear strength that was around 1.35 times higher than that of a blasted surface within an Al/FRPA hybrid.…”
Section: Introductionmentioning
confidence: 99%
“…The interlaminar strength achieved with these pin structures could exceed the strength of other presented micro structures by far. Lindner et al [13] achieved considerable adhesion with a nickel/aluminum thermal spray coating, comparable to a laser generated grid structure. The coating offered a broad variety of structure sizes as well as undercuts that were presumably beneficial for the interlaminar strength.…”
Section: Introductionmentioning
confidence: 99%